Legislative challenges on solid waste management system in Malaysia / Hamimah Abd. Hamed, Rozlya Muin and Noor Mastura Mohd Nor - Abd. Hamed, Hamimah; Muin, Rozlya; Mohd Nor, Noor Mastura (2007)
Solid Waste Management is a global issue. It has become an acute problem face by all country in the world including Malaysia. It is an ever ending issue with the emergence of new problem due to the rapid growth of population, urbanization and industrialization. In order to accomplish the status of a develop nation in 2020, efforts are been taken to over come issues relating to the management of solid waste in Malaysia. A National policy on Solid Waste was endorsed by Malaysian Cabinet 2002 where the objective is to establish a solid waste management system which is holistic, integrated and cost effective. Malaysia has decided to implement waste management by giving priority to minimizing solid waste through the 3Rs (recycle, reduce and reuse). For the past ten years, efforts have been taken by the government to establish proper and standard laws with regard to the management of solid waste. Finally in August, 2007 Malaysia has gazettes two laws relating to solid waste management namely Solid Waste Management and Public Cleansing Management Act 2007 [Act 672] and Solid Waste and Public Cleansing Management Coorperation Act 2007 [Act 673]. This project paper discuss on the pre 2007 legislation as well as the new laws which are yet to be enforced. The project paper focus on the challenges face by the new institutional frameworks in Malaysia with regard to the management of solid waste.